2020
DOI: 10.3390/ijerph17145002
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of 16–18-Year-Old Adolescents for Guiding Physical Activity Interventions: A Cross-Sectional Study

Abstract: Adolescence is a rapid life stage requiring special attention wherein personal autonomy is developed to govern independent lifestyles. Unhealthy lifestyles are integral to prevailing adolescent physical inactivity patterns. Understudied 16–18-year-olds were investigated to establish physical activity prevalences and influencing health-related lifestyle factors. Adolescents were recruited randomly across 2017–2019 from Farnborough College of Technology and North Kent College, UK. Demographic and health-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…An unhealthy lifestyle characterized by the lack of physical exercise is widespread in adolescents. Bhatti et al (2020) surveyed adolescents aged 16–18 years and found that 15% of adolescents smoked, 21% were overweight or obese, 80% did not achieve the daily required intake of vegetables and fruits, and 90% did not take enough daily exercise in the UK [ 23 ]. Moreover, 55% of adolescents do not have sufficient daily sleep or experience insomnia, 52% do not have an exercise habit, and 3% experience anxiety or depression in Taiwan [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…An unhealthy lifestyle characterized by the lack of physical exercise is widespread in adolescents. Bhatti et al (2020) surveyed adolescents aged 16–18 years and found that 15% of adolescents smoked, 21% were overweight or obese, 80% did not achieve the daily required intake of vegetables and fruits, and 90% did not take enough daily exercise in the UK [ 23 ]. Moreover, 55% of adolescents do not have sufficient daily sleep or experience insomnia, 52% do not have an exercise habit, and 3% experience anxiety or depression in Taiwan [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, among adolescents aged 16 and 17, the likelihood of accumulating behavioral risk factors is higher (Table 4 ). Older adolescents are prone to exhibit habits associated with less healthy lifestyles, such as excessive screen time [ 26 , 27 ], insufficient physical activity [ 28 , 29 ], and alcohol and tobacco consumption [ 26 ]. This increased exposure to risk factors can be attributed to reduced social constraints imposed by parents or guardians during this stage, fostering greater independence in decision-making.…”
Section: Discussionmentioning
confidence: 99%